2022
DOI: 10.3892/etm.2022.11753
|View full text |Cite
|
Sign up to set email alerts
|

Cpt1a alleviates cigarette smoke‑induced chronic obstructive pulmonary disease

Abstract: The current study aimed to determine the expression of carnitine palmitoyltransferase 1A (Cpt1a) in the lung tissue of chronic obstructive pulmonary disease (COPD) patients and its correlation with lung function. An increase in Cpt1a expression improved lung function in patients with COPD by inhibiting apoptosis and the inflammatory response of lung endothelial cells. Lung tissues of 20 patients with COPD and 10 control patients were collected, their Cpt1a expression was determined by western blotting and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
1
0
2
Order By: Relevance
“…Finally, to assess the potential interconnection of miRNAs in lung response to CS, we performed in silico prediction of hsa-miR target genes. Bioinformatic results revealed that the miRNAs analyzed may potentially be involved in the regulation of several inflammation driver genes, such as ATG14, BCL2, CPT1A, FOXC1, HAS2, HSPA1A, LAMTOR1, MCL1, MFN2, SCAMP5, SENP1, SOCS5, TGFBR2 and VEGFA, which are involved in immune system regulatory pathways [74][75][76][77][78][79][80][81][82][83][84][85][86][87]. Since several authors have experimentally…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to assess the potential interconnection of miRNAs in lung response to CS, we performed in silico prediction of hsa-miR target genes. Bioinformatic results revealed that the miRNAs analyzed may potentially be involved in the regulation of several inflammation driver genes, such as ATG14, BCL2, CPT1A, FOXC1, HAS2, HSPA1A, LAMTOR1, MCL1, MFN2, SCAMP5, SENP1, SOCS5, TGFBR2 and VEGFA, which are involved in immune system regulatory pathways [74][75][76][77][78][79][80][81][82][83][84][85][86][87]. Since several authors have experimentally…”
Section: Discussionmentioning
confidence: 99%
“…Наряду с этим, данные многочисленных экспериментальных работ демонстрируют такие свойства L-карнитина как антиоксидантный эффект [1,2,[8][9][10][11], возможность коррекции эндотелиальной дисфункции [8][9][10][11][12], влияние на процессы апоптоза и воспаления в различных тканях [11][12][13]. Механизмы описанных эффектов L-карнитина до настоящего времени остаются неясными.…”
unclassified
“…В этой связи представляется интересной концепция карнитинового гомеостаза S. ранее предложенная S. Sharma и соавторами, которая связывает содержание L-карнитина, его ацильных производных и активность карнитинпальмитоилтрансфераз с NO (II) опосредованной передачей сигналов и функцией митохондрий в клетках эндотелия легочной артерии [11]. Эта взаимосвязь подтверждается в более поздних работах связанных с эндотелиальной дисфункцией на фоне диабета, однако исследование этой связи в других органах остается малоизученным, что и стало целью текущей работы [10][11][12][13].…”
unclassified